Social workers’ psychosocial interventions with child secondary victims of genderbased violence: a case of four major townships in Johannesburg, South Africa. - Dlamini, Muriel (My University, 2023)
Gender-based violence (GBV) is a global pandemic that threatens the future of many generations. GBV does not only affect its direct victims but also children who witness it, who then become child secondary victims. Left unaddressed or unspoken, these unfortunate events can affect both their present (childhood) and future lives (adulthood). Globally, South Africa is among the leading countries facing GBV woes. This calls for more intervention, especially for children exposed to violence at home and in their respective communities. Psychosocial interventions by social workers are therefore crucial in assisting children who are secondary victims of domestic and gender-based violence. The study aimed to explore psychosocial interventions used by social workers to address the effects caused by GBV on children. The study employed a qualitative research approach and adopted a case study design. Eight social workers from organizations in four townships (Alexandra, Diepsloot, Soweto, and Tembisa), who have worked with child victims of GBV were interviewed. The participants were invited through snowball sampling techniques. Data was collected through one-on-one individual interviews using a semi-structured interview schedule as a research tool. The data collected was analysed through manual thematic analysis. The findings of this study revealed that there is a need for child secondary victims of GBV to get access to counselling services after witnessing violence at home as a way of processing and dealing with psychological trauma. They also revealed that, while there is no stipulated intervention used when working with child secondary victims of GBV, the use of more holistic ways of intervention has proven much more effective. Recommendations are made for future research and these call for the need for collaboration between the departments of Basic Education and Social Development, as well as other health professionals, to help curb the negative effects caused by exposure to GBV on children.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2023